Global Community in James Welch’s The Heartsong of Charging Elk - Kedong Liu; Yutong Zhao; Limin Li (Humanities)
Human beings have had beautiful dreams for a harmonious world since centuries ago; this can be termed cosmopolitanism, shijie datong, or global community. Based on theories expounded by Confucius, Tönnies, Anderson, Bauman, Derrida, and Appiah, we closely examine the concept of “global cultural community” or “international community”, that is, the community involving individuals or groups of two or more countries by way of textual analysis, with James Welch’s The Heartsong of Charging Elk as an example. Through an analysis of the plot in the novel, we find that the American Indian protagonist Charging Elk integrates into the local French culture, while retaining his indigenous cultural identity, and thus negotiates a global community. This finding is also evaluated in the context of all five novels by Welch and in a broader scope of American Indian literature with inter-continental themes. The studies on cosmopolitanism or global community in American Indian literature can play an important role in exploring the construction of a global community for humanity for a shared future.